EFFECT OF POST-HARVEST GREENING ON SPROUTING BEHAVIOUR OF POTATO TUBERS UNDER CONTROLLED CONDITIONS - Singh, Brajesh; Ezekiel, R; Mehta, Ashiv (Potato Journal, 2013)
Post harvest greening of potato tubers for 25 days by exposing them to natural sunlight and artificial fluorescent light resulted in higher accumulation of chlorophyll in cvs. Kufri Jyoti and Kufri Lalima in comparison to the tubers stored in dark. There was no effect of greening on dormancy release, sprout growth and weight loss in these two potato cultivars and most of the observed parameters remained unaffected by greening.